Doses de fomesafen e populações de plantas no controle de plantas daninhas e nas culturas do feijão e sorgo em sucessão - Silva, Laís de Oliveira (2016)
In the common bean crop, one of the main responsible factors for low productivity is the weed competition by water, light and nutrients and thus its chemical control is an important operation in production systems, in order to reduce and, or eliminate the undesirable effects of interference. The objective was to evaluate the phytotoxicity and weed control by fomesafen in bean crop and its residual activity on sorghum crop in succession. The experiments were conducted in the south of Minas Gerais state, at the Lambari Experimental Farm of the Empresa de Pesquisa Agropecuária de Minas Gerais, in autumn winter season and Muquém Experimental Farm of the Federal University of Lavras, in the rainy season. The experimental design was a randomized block, with three replications and a factorial 4 x 4, with four doses of fomesafen (0.5, 1.0, 1.5 and 2.0 L.ha -1 ) and four bean plant populations (120, 200, 280 and 360 000 plants. ha -1 at Lambari and 120, 160, 200 and 240 000 plants.ha -1 at Lavras). Sowing sorghum was carried out in succession to the beans, 89 days after application of fomesafen. It was identified 11 weed species at Lambari, with fomesafen phytotoxicity on potato, nutsedge, bermudagrass and ipecac, and 14 species at Lavras, including crabgrass, dairy and mentrasto that it showed phytotoxicity. The sorghum characteristics were not influenced by bean populations and herbicide doses, which it did not interfere on the sorghum development and productivity. Thus, the fomesafen showed selective for bean, not interfering on the production characteristics and the herbicide doses left no residue on the sorghum crop in succession.